PENERAPAN STRATEGI ACTIVE LEARNING BERMUATAN KARAKTER TERHADAP KEJENUHAN BELAJAR MATEMATIKA SISWA DI SDIT RR CURUP TENGAH - Syaripah Syaripah; M. Rustan Nasrudin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
This research uses this type of research is quantitative descriptive research with active learning strategies. The population of the study i.e. the whole grade IV SDIT Rabbi Radhiyya Curup Middle amounted to 40 students. The sample in this research is the IVC classes totalling 25 students. Research that has been conducted showed how saturation study grade IV in the SDIT Rabbi Radhiyya with the number of students is 25 people. Note that the results of the now burning out student learning can be found in the category 10 students (40%) with the value of the 54 students who got up, the value of the category were as much as 3 students (12%) with the value 52-53 and the students who get the value in the low category as many as 12 students (48%) with the value 51 down. Then be consulted on the t_hitung of 4.59 after consulted on t_tabel of 2.07 obtained the conclusion that t_hitung > t_tabel i.e. 4.59 > 2.07. Therefore, the Ha received namely electrically active learning strategies influence the characters against the saturation study grade IV in the SDIT Rabbi RadhiyyaKeywords: quantitative descriptive research, active learning strategies, the saturation study.